Clinical teaching and learning within a preceptorship model in an acute care hospital in Ireland; a qualitative study. (April 2017) - McSharry, Edel; Lathlean, Judith
Abstract: Background: A preceptorship model of clinical teaching was introduced to support the new all-graduate nurse education programme in Ireland in 2002. Little is known about how this model impacts upon the pedagogical practices of the preceptor or student learning in clinical practice leading to question what constitutes effective teaching and learning in clinical practice at undergraduate level. Aim: This study aimed to explore the clinical teaching and learning within a preceptorship model in an acute care hospital in Ireland and identify when best practice, based on current theoretical professional and educational principles occurred. Method: A qualitative research study of a purposively selected sample of 13 students and 13 preceptors, working together in four clinical areas in one hospital in Ireland. Methods were semi-structured interviews, analysed thematically, complemented by documentary analysis relating to the teaching and assessment of the students. Ethical approval was gained from the hospital's Ethics Committee. Findings: Preceptor-student contact time within an empowering student-preceptor learning relationship was the foundation of effective teaching and learning and assessment. Dialoguing and talking through practice enhanced the students' knowledge and understanding, while the ability of the preceptor to ask higher order questions promoted the students' clinical reasoning and problem solving skills. Insufficient time to teach, and an over reliance on students' ability to participate in and contribute to practice with minimal guidance were found to negatively impact students' learning. Conclusions & Implications: Concepts such as cognitive apprenticeship, scaffolding and learning in communities of practice can be helpful in understanding the processes entailed in preceptorship. Preceptors need extensive educational preparation and support to ensure they have the pedagogical competencies necessary to provide the cognitive teaching techniques that foster professional performance and clinical reasoning. National competency based standards for preceptor preparation should be developed. Highlights: A qualitative study exploring teaching and learning in a preceptorship model Working alongside and talking through practice enhanced the students' learning. Preceptors who asked higher order questions promoted students' clinical reasoning. Cognitive apprenticeship provides an educational framework for preceptorship. Preceptors need to be pedagogically competent.